2014
DOI: 10.3402/jchimp.v4.25418
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell trait: not as benign as once thought

Abstract: We describe a case of renal papillary necrosis in a middle-aged female with sickle cell trait who presented with gross hematuria. We wish to highlight this case for several reasons. Sickle cell trait is often viewed as a benign condition despite the fact that it is associated with significant morbidity such as renal papillary necrosis and renal medullary carcinoma. Appropriate evaluation needs to be undertaken to promptly diagnose renal papillary necrosis and differentiate it from renal medullary carcinoma as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Although children with sickle cell anemia are identified as high risk for IPD, this does not extend to sickle cell trait, the carrier status of the disease. Historically, sickle cell trait has been considered benign, yet recent reports demonstrate that it may be less asymptomatic than previously thought . For example, children with sickle cell trait are at an increased risk of IPD as compared to children with normal hemoglobin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although children with sickle cell anemia are identified as high risk for IPD, this does not extend to sickle cell trait, the carrier status of the disease. Historically, sickle cell trait has been considered benign, yet recent reports demonstrate that it may be less asymptomatic than previously thought . For example, children with sickle cell trait are at an increased risk of IPD as compared to children with normal hemoglobin .…”
Section: Introductionmentioning
confidence: 99%
“…Historically, sickle cell trait has been considered benign, 13,14 yet recent reports demonstrate that it may be less asymptomatic than previously thought. 13,15,16 For example, children with sickle cell trait are at an increased risk of IPD as compared to children with normal hemoglobin. 17 Yet, nothing is known regarding the pneumococcal vaccination coverage among children with sickle cell trait.…”
Section: Introductionmentioning
confidence: 99%
“…Patients may also experience episodes of hematuria spontaneously or with heavy physical exertion. The pathophysiology behind this is due to the microvascular obstruction by rigid erythrocytes, which will lead to tissue necrosis and renal papillary infarcts causing the hematuria [ 13 , 14 ]. Many studies have identified that patients with SCT are at an increased risk of exertional rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a case of Hodgkin's lymphoma causing hepatic failure and a case of amyloidosis causing heart failure ( 13 , 14 ). Sickle cell trait-induced papillary necrosis is reported – a very unusual complication for this typically mild problem ( 15 ). There is a report of neuroendocrine prostate cancer with normal PSA levels ( 16 ).…”
Section: And Beyondmentioning
confidence: 99%